Outbursts of the intermediate-mass black hole HLX-1: a wind-instability scenario - Soria, Roberto; Musaeva, A.; Wu, K.; Zampieri, L.; Federle, S.; Urquhart, Ryan; van der Helm, E.; Farrell, S. (Oxford University Press, 2017)
We model the intermediate-mass black hole HLX-1, using the Hubble Space Telescope, XMM–Newton and Swift. We quantify the relative contributions of a bluer component, function of X-ray irradiation, and a redder component, constant and likely coming from an old stellar population. We estimate a black hole mass ≈(2+2−1)×104M⊙ , a spin parameter a/M ≈ 0.9 for moderately face-on view and a peak outburst luminosity ≈0.3 times the Eddington luminosity. We discuss the discrepancy between the characteristic sizes inferred from the short X-ray time-scale (R ∼ a few 1011 cm) and from the optical emitter ( Rcosθ−−−−√≈2.2×1013 cm). One possibility is that the optical emitter is a circumbinary disc; however, we disfavour this scenario because it would require a very small donor star. A more plausible scenario is that the disc is large but only the inner annuli are involved in the X-ray outburst. We propose that the recurrent outbursts are caused by an accretion-rate oscillation driven by wind instability in the inner disc. We argue that the system has a long-term-average accretion rate of a few per cent Eddington, just below the upper limit of the low/hard state; a wind-driven oscillation can trigger transitions to the high/soft state, with a recurrence period ∼1 yr (much longer than the binary period, which we estimate as ∼10 d). The oscillation that dominated the system in the last decade is now damped such that the accretion rate no longer reaches the level required to trigger a transition. Finally, we highlight similarities between disc winds in HLX-1 and in the Galactic black hole V404 Cyg.